The role of teachers in encouraging DL-Mobile - Darmawan, Deni; Yusup, Ade; Fauziyyah, Ayu F.; Ulfah, Pipit F.; Permana, Fadillah (International Journal Labs, 2024)
The use of mobile phones by students is increasingly widespread, both for learning purposes and for other personal purposes. As mobile technology continues to permeate students' lives, mobile DL-Mobile is important for students to be able to utilize mobile technology optimally and responsibly. This article discusses the role of teachers in promoting Digital Literacy Mobile (DL- Mobile) among students. The findings of this article provide valuable insights into the strategies and approaches teachers use to encourage digital literacy in the mobile era, offering practical implications for improving educational practices. The study highlights how educators serve as key facilitators in integrating mobile technology into the learning environment, thereby enhancing students' digital competencies. Teachers can increase students' awareness of the importance of mobile technology in their daily lives and improve their ability to use social media effectively to gather information. The results of this study can be used to improve the quality of education and improve students' ability to face increasingly complex global challenges that require better digital skills.